Review of Conductive Reciprocating Liquid Metal Magnetohydrodynamic Generators - Lingzhi Zhao; Aiwu Peng (Energies)
Reciprocating liquid metal magnetohydrodynamic (MHD) power generation is a new MHD power generation method in which the working fluid is a single-phase liquid metal with a low melting point and high conductivity. The internal combustion stroke of automobiles, ocean waves, sound waves and other reciprocating external forces drive the liquid metal to flow back and forth in an applied magnetic field, generating single-phase alternating current (AC) energy. Reciprocating liquid metal MHD (LMMHD) power generation has the advantages of a high power density, high efficiency, a fast start and good stability, and it provides a new solution for space static nuclear power conversion, variable-stroke automobile engines, distributed power supply and ocean energy utilization. According to the mode of action of an electromagnetic field, reciprocating LMMHD generators can be divided into the inductive type and conductive type. Compared with the inductive type, the conductive type has a simple structure and is the current research hot spot. Firstly, the classification and characteristics of reciprocating LMMHD power generation are introduced. Then, the working characteristics of conductive reciprocating LMMHD (CRLMMHD) generators are analyzed. On this basis, technical key points and issues in the current research of CRLMMHD generators are elaborated. Finally, conclusions and the future research direction of CRLMMHD generators are pointed out.